Riskscapes: Strategies and Practices Along the Georgian–Abkhazian Boundary Line and Inside Abkhazia. Issue 4 (2nd October 2018) - Lundgren, Minna
ABSTRACT: The Georgian–Abkhazian war in 1992–1993 caused the forced displacement of around half of the population of the former autonomous Abkhazian republic. Over 200, 000 of them were ethnic Georgians, out of whom at least 46, 000 have returned mainly to southern Abkhazia. Abkhazia today functions as a de facto independent state, and the Russian–Abkhazian border control along the administrative boundary line between Abkhazia and Georgia poses an obstacle to young people from returnee families who are studying in Georgia proper and want to visit their families in Abkhazia. This study focuses on young migrants navigating the consequences of war and ethnic conflict on human mobility in the border area. Drawing on ethnographic fieldwork and five in-depth qualitative interviews with young people aged 18–25 years, the aim is to examine the strategies and practices that the young respondents employ to cross the border. To reach their homes in Abkhazia they need to navigate through riskscapes—landscapes or physical settings embedded with multiple layers of risk. Depending on their social positions (gender, ethnicity, citizenship, age) different riskscapes are unfolded. To handle riskscapes these young people adopt preventive measures; they change routes and behavior.